Intra-articular depletion of macrophages increases acute synovitis and alters macrophage polarity in the injured mouse knee. Issue 5 (May 2020) - Bailey, K.N.; Furman, B.D.; Zeitlin, J.; Kimmerling, K.A.; Wu, C.-L.; Guilak, F.; Olson, S.A.
Summary: Objective: Acute synovial inflammation following joint trauma is associated with posttraumatic arthritis. Synovial macrophages have been implicated in degenerative changes. In this study, we sought to elucidate the role of intra-articular macrophages in the acute inflammatory response to fracture in the mouse knee. Method: A closed articular fracture was induced in two models of synovial macrophage depletion: genetically-modified MaFIA mice administered AP20187 to induce programmed macrophage apoptosis, and wild-type C57BL/6 mice administered clodronate liposomes, both via intra-articular injection. Synovial inflammation, bone morphology, and levels of F4/80+ macrophages, NOS2+ M1 macrophages, and CD206+ M2 macrophages were quantified 7 days after fracture using histology and micro-computed tomography. Results: Intra-articular macrophage depletion with joint injury did not reduce acute synovitis or the number of synovial macrophages 7 days after fracture in either macrophage-depleted MaFIA mice or in clodronate-treated C57BL/6 mice. In macrophage-depleted MaFIA mice, macrophage polarity shifted to a dominance of M1 macrophages and a reduction of M2 macrophages in the synovial stroma, indicating a shift in M1/M2 macrophage ratio in the joint following injury. Interestingly, MaFIA mice depleted 2 days prior to fracture demonstrated increased synovitis ( P  = 0.003), reduced bone mineral density ( P  = 0.0004), higher levels of M1 macrophages ( P  = 0.013), and lower levels of M2 macrophages ( not statistically significant, P = 0.084 ) compared to control-treated MaFIA mice. Conclusion: Our findings indicate that macrophages play a critical immunomodulatory role in the acute inflammatory response surrounding joint injury and suggest that inhibition of macrophage function can have prominent effects on joint inflammation and bone homeostasis after joint trauma.